188k views
3 votes
(6-3(cube root of 6)/(cube root of 9)

User Jvstech
by
5.4k points

1 Answer

7 votes

For this case we must simplify the following expression:


\frac {6-3 \sqrt [3] {6}} {\sqrt [3] {9}}

Multiplying the numerator and denominator by
(\sqrt [3] {9}) ^ 2


\frac {6-3 \sqrt [3] {6}} {\sqrt [3] {9}} * \frac {(\sqrt [3] {9}) ^ 2} {(\sqrt [3] { 9}) ^ 2} =

We rewrite:


\frac {\frac {6-3 \sqrt [3] {6}} * (\sqrt [3] {9}) ^ 2} {\sqrt [3] {9} * (\sqrt [3] {9 }) ^ 2} =

By properties of powers we have that:


a ^ m * a ^ n = a ^ {m + n}\\\frac {(6-3 \sqrt [3] {6}) * (\sqrt [3] {9}) ^ 2} {(\sqrt [3] {9}) ^ 3} =\\\frac {(6-3 \sqrt [3] {6}) * (\sqrt [3] {9}) ^ 2} {9} =

We rewrite, moving the exponent within the radical:


\frac {(6-3 \sqrt [3] {6}) * \sqrt [3] {9 ^ 2}} {9} =\\\frac {(6-3 \sqrt [3] {6}) * \sqrt [3] {81}} {9} =

We can rewrite
3 * 3 ^ 3 = 81


\frac {(6-3 \sqrt [3] {6}) * \sqrt [3] {3 * 3 ^ 3}} {9} =

We simplify:


\frac {(6-3 \sqrt [3] {6}) * 3 \sqrt [3] {3}} {9} =

We apply distributive property:


\frac {18 \sqrt [3] {3} -9 \sqrt [3] {18}} {9} =

Simplifying we finally have:


2 \sqrt [3] {3} - \sqrt [3] {18}

Answer:


2 \sqrt [3] {3} - \sqrt [3] {18}

User Egbrad
by
5.7k points